Impacts of Delivery Mode and Maternal Factors on Neonatal Oral Microbiota - Xu, Tiansong; Yan, Lihuang; Sun, Bohui; Xu, Qi; Zhang, Jieni; Zhu, Wenhui; Zhang, Qian; Chen, Ning; Liu, Guoli; Chen, Feng (Frontiers in Microbiology, 2022)
Objectives Initial oral microbial colonization has complicatedly interacted with growth and development. The aim of our study was to discover links between oral microbiota community structure and mode of delivery, maternal factors, such as systemic diseases, abortion history, and pregnancy complications. Methods A total of 177 pregnant women and their neonates were enrolled at Peking university people’s hospital. We collected oral samples, medical history, and development phenotype and used a 16S rRNA gene sequence to analyze microbial diversity at all taxonomic levels, network structure, and metabolic characteristics. Results Firmicutes, Proteobacteria, and Actinobacteriota were the most predominant bacteria of neonatal oral samples among these phyla. Alpha-diversity of pregnant women with gestational diabetes mellitus (GDM), abortion history, and without immune diseases was higher than in control groups, and no significant dissimilarity in beta-diversity was observed between different maternal factors. Obvious separation or trend failed to be seen in different development phenotype groups. Besides, Oscillospirales were significantly more abundant in a natural delivery group than in the cesarean section group. Conclusion Our study indicated that maternal factors and mode of delivery influenced the oral microbial structure, but longitudinal studies were indispensable for capturing the long-term effects on neonatal development phenotype and oral microbiota.